2021
DOI: 10.3390/molecules26103027
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial, Antifungal and Antibiofilm Activities of Silver Nanoparticles Supported by Crude Bioactive Metabolites of Bionanofactories Isolated from Lake Mariout

Abstract: Lake Mariout is one of the polluted coastal marine ecosystems in Egypt which is considered to be a reservoir of serious effluents from different anthropogenic activities. Such selective pressure enforces indigenous microbial populations to acquire new advantageous themes. Thus, in this study, two Streptomyces strains were screened, from Lake Mariout’s sediment for bioreduction of 5 mM AgNO3. Both strains were identified molecularly; their biochemical and physiological characterization revealed their ability to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 68 publications
2
12
0
Order By: Relevance
“…Finally, the band at the 536 cm −1 region is most likely credited to C-Br stretching, which is typical of alkyl halides [93]. Other investigations reported that peaks at minor field in the range 400-700 cm −1 reflected the metallic nature of any examined sample, Ag NPs in our case [94]. As stated before, these functional groups, in general, have a role in the stability/capping of Ag NPs as reported in many studies [95][96][97][98].…”
Section: Ftir Spectrum Analysis For Ag Npssupporting
confidence: 57%
“…Finally, the band at the 536 cm −1 region is most likely credited to C-Br stretching, which is typical of alkyl halides [93]. Other investigations reported that peaks at minor field in the range 400-700 cm −1 reflected the metallic nature of any examined sample, Ag NPs in our case [94]. As stated before, these functional groups, in general, have a role in the stability/capping of Ag NPs as reported in many studies [95][96][97][98].…”
Section: Ftir Spectrum Analysis For Ag Npssupporting
confidence: 57%
“…Such strains were isolated from different ecosystems that contained different pollutant loads. They exhibited characteristic biochemical and physiological capabilities and some of them were utilized previously in the bioremediation of heavy metals [ 58 ]. As noticed, the selected strains are affiliated to different bacterial classes encompassing alphaproteobacteria , gammaproteobacterial and firmicutes , which imply different behaviors in terms of the handling of substrates.…”
Section: Resultsmentioning
confidence: 99%
“…Dehydrated and lyophilized samples were triturated into fine powder, combined with KBr (1.0 percent w / w ) and crushed into transparent discs in a hydraulic press. Spectra were captured at 4 cm −1 resolution over a range of 4000–400 cm −1 with an accumulation of 64 scans and using dried air as a background [ 58 ].…”
Section: Methodsmentioning
confidence: 99%
“…Such fungal infections appeared recently in the second wave in India, in particular in patients who were put on mechanical ventilation in intensive—care units. The fungicidal property of Ag@Ag 2 ONCs could be assigned to the damage of the glycoprotein-glucan-chitin cross-linkage of fungi cell wall followed by sever alterations in cellular biochemistry 11 , 45 . In addition, it has been suggested that Ag nanoparticles interact with the proteins of the plasma membrane, which is responsible for keeping trans-membrane electrochemical potential gradient such as H + ATPase protein.…”
Section: Resultsmentioning
confidence: 99%